The Godoy & Godoy cervical stimulation technique in the treatment of primary congenital lymphedema - Jose Maria Pereira de Godoy; Ana Carolina Pereira de Godoy; Tania Dias Guimarães; Maria de Fatima Guerreiro Godoy (MDPI AG, 2012)
The aim of the current study is to report on the treatment of primary lymphedema using a new form of therapy: cervical stimulation. In a prospective cohort study, 9 boys and 5 girls with primary congenital lymphedema were evaluated over two years. Age ranged from two months to 8.5 years. After diagnosis, all mothers were trained in the new technique. The Godoy & Godoy cervical stimulation technique consists of between 20 to 30 stimuli per minute using light movements in the cervical region. All the children were submitted to perimetric evaluations of the feet and legs; however, in this study only two points, 3 and 6 cm from the base of the big toe nail, were used. The two-tailed t-test was used for statistical analysis with an alpha error of 5% (P<0.05) considered acceptable. The size of the lymphedematous feet was reduced and even normalized (P<0.0001) for all treated children. Cervical stimulation is a new option in the treatment of primary congenital lymphedema; its association with compression stockings has a synergistic effect in reducing the volume of lymphedema.